Protective Role for Smooth Muscle Cell Hepcidin in Abdominal Aortic Aneurysm. Issue 5 (27th April 2023) - Loick, Paul; Mohammad, Goran Hamid; Cassimjee, Ismail; Chandrashekar, Anirudh; Lapolla, Pierfrancesco; Carrington, Alison; Vera-Aviles, Mayra; Handa, Ashok; Lee, Regent; Lakhal-Littleton, Samira
Abstract : Background: Hepcidin is a liver-derived hormone that controls systemic iron homeostasis, by inhibiting the iron exporter ferroportin in the gut and spleen, respective sites of iron absorption and recycling. Hepcidin is also expressed ectopically in the context of cardiovascular disease. However, the precise role of ectopic hepcidin in underlying pathophysiology is unknown. In patients with abdominal aortic aneurysm (AAA), hepcidin is markedly induced in smooth muscle cells (SMCs) of the aneurysm wall and inversely correlated with the expression of LCN2 (lipocalin-2), a protein implicated in AAA pathology. In addition, plasma hepcidin levels were inversely correlated with aneurysm growth, suggesting hepcidin has a potential disease-modifying role. Methods: To probe the role of SMC-derived hepcidin in the setting of AAA, we applied AngII (Angiotensin-II)-induced AAA model to mice harbouring an inducible, SMC-specific deletion of hepcidin. To determine whether SMC-derived hepcidin acted cell-autonomously, we also used mice harboring an inducible SMC-specific knock-in of hepcidin-resistant ferroportinC326Y. The involvement of LCN2 was established using a LCN2-neutralizing antibody. Results: Mice with SMC-specific deletion of hepcidin or knock-in of hepcidin-resistant ferroportinC326Y had a heightened AAA phenotype compared with controls. In both models, SMCs exhibited raised ferroportin expression and reduced iron retention, accompanied by failure to suppress LCN2, impaired autophagy in SMCs, and greater aortic neutrophil infiltration. Pretreatment with LCN2-neutralizing antibody restored autophagy, reduced neutrophil infiltration, and prevented the heightened AAA phenotype. Finally, plasma hepcidin levels were consistently lower in mice with SMC-specific deletion of hepcidin than in controls, indicating that SMC-derived hepcidin contributes to the circulating pool in AAA. Conclusions: Hepcidin elevation in SMCs plays a protective role in the setting of AAA. These findings are the first demonstration of a protective rather than deleterious role for hepcidin in cardiovascular disease. They highlight the need to further explore the prognostic and therapeutic value of hepcidin outside disorders of iron homeostasis.